Sorption behavior and isosteric heat of maize-millet based protein enriched extruded product. Issue 4 (April 2021) - Sahu, Chandrahas; Patel, Shadanan; Khokhar, Dharmendra
Abstract: Moisture sorption behaviour and isosteric heat of sorption are essential to be familiar with the stability of products, various storage condition and selection of packaging materials. Sorption behavior of extruded product was done at 30, 40, 50 and 60 °C temperatures under 11–92% relative humidity. The product was developed from an optimized blend of maize, defatted soy, finger millet and yam at an optimum condition of 14% (wb) feed moisture, 110 °C barrel temperature and 301 rpm screw speed. The net isosteric heat of sorption of the extruded product was determined by using Clausius-Clapeyron equation. The equilibrium moisture content (EMC) was found to be raised with the rise in water activity (aw ) in particular temperature. The highest EMC 30.05% (db) was recorded at 0.92 aw and 30 °C temperature, whereas the lowest EMC 2.46% (db) at 0.11 aw and 60 °C temperature. The isotherms exhibits curves of Type-II for four temperature conditions. The EMC data were fitted to six sorption models and GAB model was found to be best fitted among them. The net isosteric heat of sorption varied between 16.711 and 3.242 kJ/mol within 5–30% (db) of sample moisture content. Abstract : Equilibrium moisture content; extruded product; net isosteric heat; relative humidity; temperature condition; water activity.